Functional Change of Effector Tumor-Infiltrating CCR5+CD38+HLA-DR+CD8+ T Cells in Glioma Microenvironment - Chen, Pin-Yuan; Wu, Caren Yu-Ju; Fang, Jian-He; Chen, Hsiu-Chi; Feng, Li-Ying; Huang, Chiung-Yin; Wei, Kuo-Chen; Fang, Jia-You; Lin, Chun-Yen (Frontiers in Immunology, 2019)
Human glioma facilitates an impaired anti-tumor immunity response, including defects in circulation of T lymphocytes. The level of CD8+ T-cell activation acts as an immune regulator associated with disease progression. However, little is known about the characteristics of peripheral and tumor-infiltrating CD8+ T cells in patients with glioma. In this study, we examined the level of CD8+ T-cell activation in a group of 143 patients with glioma and determined that peripheral CD3+ T cells decreased in accordance with disease severity. The patients’ peripheral CD8+ T-cell populations were similar to that of healthy donors, and a small amount of CD8+ tumor-infiltrating lymphocytes was identified in glioma tissues. An increase in activated CD8+ T cells, characterized as CD38+HLA-DR+, and their association with disease progression were identified in the patients’ peripheral blood and glioma, and shown to display enriched CCR5+ and TNFR2+ expression levels. Ex vivo examination of CD38+HLA-DR+CD8+ T cells indicated that this subset of cells displayed stronger secretion of IFN-γ and IL-2 before and after a 6-h stimulation with phorbol 12-myristate 13-acetate (PMA) and ionomycin (ION) relative to healthy CD38+HLA-DR+CD8+ T cells, indicating the functional feasibility of CD38+HLA-DR+CD8+ T cells. Higher CCL5 protein and mRNA levels were identified in glioma tissues, which was consistent with the immunohistochemistry results revealing both CCL5 and CD38+HLA-DR+CD8+ T cell expression. Patients’ CCR5+CD38+HLA-DR+CD8+ T cells were further validated and shown to display increases in CD45RA+CCR7- and T-bet+ accompanied by substantial CD107-a, IFN-γ, and Granzyme B levels in response to glioma cells.